EFEKTIVITAS METODE EXTENDING CONCEPT THROUGH LANGUAGE ACTIVITIES (ECOLA) DALAM MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS SISWA KELAS X SMA NEGERI 1 ENREKANG - Abu Bakar Tumpu; Jumriati Jumriati (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2018)
This study aims to examine the effectiveness of the Extending Concept Method Through Language Activities (ECOLA) in Improving Reading Comprehension Skills for Class X Students of Enrekang 1 High School and to examine the effectiveness of student learning outcomes by using Extending Concept Method Through Language Activities (ECOLA) with conventional models in improving refined text reading skills. The type of research used is a quantitative approach with method expriment. The research variable consists of two, namely the application of the Extending Concept strategy method through Language Activities (ECOLA) as an independent variable (X) and learning to write letters as dependent variables (Y). The research design used in this study was experimental research using a quasi-experimental method with the initial test design and final test of the control group and experimental group with random samples (Therandomized pretest-posttest control grouf design. The results of this study indicate Extending Concept methods Through Language Activities ( ECOLA) is effective in improving the reading skills of text comprehension in class X students of SMA Enrekang 1 and there are differences in the effectiveness of student learning outcomes by using the Extending Concept method Through Language Activities (ECOLA) with conventional models in improving reading comprehension skills.Keywords: Extending Concept Through Language Activities, Reading Understanding.